Expanded newborn screening: Guiding principles, concerns and relevance - Seema Pavaman Sindgikar; Rathika Damodar Shenoy (Wolters Kluwer Medknow Publications, 2014)
Since its introduction in 1960s, universal newborn screening (NBS) using the heel-prick dried blood spot samples has become an integral part of public health system in developed countries expanded to pre-symptomatic detection of specific inherited metabolic, endocrine and hematologic disorders. In our country, NBS may become relevant with epidemiological shift and increasing access to technology. Current recommendations include a phased introduction of screening for congenital hypothyroidism, congenital adrenal hyperplasia and glucose 6-phosphate dehydrogenase deficiency. In this review, the guiding principles of NBS, some of the individual disorders, the concerns and relevance to our country are discussed. Establishing a pre- and post-screening care and education are of utmost priority before NBS is adapted into health care system.